Arbuscular mycorrhizas and performance of Polylepis australis trees in relation to livestock density - Menoyo, Eugenia (2009)
Polylepis australis trees endemic to Argentina dominate the canopy of subtropical high altitude forests. Here, livestock rearing is the main economic activity and is suspect of the low performance of P. australis trees through direct and indirect effects which could include the reduction in arbuscular mycorrhizal fungi (AMF) and their benefit to trees. To elucidate the role of AMF, we compare plant performance indicators, arbuscular mycorrhizal (AM) colonization and AMF communities in 20 trees distributed in two areas of central Argentina which differed in livestock grazing intensity. The area with high livestock density presented more soil degradation and trees with a lower overall plant performance than the area with reduced livestock density. The AM colonization values of P. australis were considerably higher than reported for other tree species and the area with high livestock density had a lower proportion of arbuscules and higher proportion of hyphae, while vesicles and AM colonization -all structure considered together- did not differ between areas. Overall AMF spore number and of most species when considered separately was significantly higher in the area with high livestock density, suggesting a high tolerance and adaptation of AMF to livestock. We conclude that a reduction in livestock improves the performance of P. australis, that this improvement could be mediated by an increase in the proportion of arbuscules, but there does not appear to be any limitation in AM colonization or AMF spore number which could otherwise be limiting forest restoration.